Optimization of a new type of hysteresis motor using genetic algorithm - Sadeghi, M H; Darabi, A (2010 9th International Conference on Environment and Electrical Engineering, 2010)
HYSTERESIS motors are self-starting synchronous motors that take advantage of the hysteresis characteristics of the magnetic materials. Robust structure, flat speed-torque characteristics, smooth operation and constant low starting current are the outstanding specifications of these machines. Nevertheless, low efficiency and low power factor are among the disadvantages of common hysteresis motors. Very recently, Coreless Dual Discs Hysteresis Motor (CDDHM) has been introduced to enhance the efficiency of the hysteresis motors. So far, design algorithm and impacts of the design parameters on the performance of the CDDHM have not been fully investigated. Conventional optimization algorithms commonly are employed to solve the linear problems and those are not easily applicable for design optimization of a hysteresis machine with a complicated, nonlinear and multi values model. These difficulties are mainly due to the fact that the output torque of a flat hysteresis motor is proportionally related to area of the hysteresis loops on volume of the rotor discs. This paper presents an initial design algorithm and then describes application of a genetic algorithm-based approach with all details solving successfully the maximum efficiency optimization problem of a CDDHM. The output power and efficiency obtained from theory is shown to be in good agreement with the measured values.